1992
DOI: 10.1007/bf03214723
|View full text |Cite
|
Sign up to set email alerts
|

A new high strength gold bond wire

Abstract: As semiconductor technology develops, conventional bond wires are reaching the limits of their capability. Industry is demanding finer diameter wire coupled with higher strength, and the retention of this strength at elevated temperatures would be a decided advantage.It has been demonstrated that a fine wire of the composition Au-lwt.%Ti, which was originally formulated for high carat jewellery, can be endowed with these beneficial properties by appropriate thermomechanical treatments. A three-fold increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Although the ultimate tensile strength of 550 MPa at T)=5.6 for the Au-lOAg DMMC is much higher than the strength of pure annealed gold, it is lower than the ultimate tensile strength of several precipitationhardened gold alloys (egAu-1 wt%Ti with (JUTS = 1000 MPa) (20). It remains for future studies to determine whether deformation beyond T)=5.6 would further strengthen an Au-lOAg DMMC and whether the 10% Ag volume is optimal.…”
Section: Potential For Further Developmentmentioning
confidence: 81%
“…Although the ultimate tensile strength of 550 MPa at T)=5.6 for the Au-lOAg DMMC is much higher than the strength of pure annealed gold, it is lower than the ultimate tensile strength of several precipitationhardened gold alloys (egAu-1 wt%Ti with (JUTS = 1000 MPa) (20). It remains for future studies to determine whether deformation beyond T)=5.6 would further strengthen an Au-lOAg DMMC and whether the 10% Ag volume is optimal.…”
Section: Potential For Further Developmentmentioning
confidence: 81%
“…Work hardening is therefore increased by solid solution hardening and grain refining effects, leading to much higher strengthening levels and also to increased recrystallization temperatures (22). Precipitation hardening, which gives stronger effects than those of the doping elements discussed above, can be obtained, for example by titanium (23,24). However, this approach is not yet commonly used because it is generated mainly by alloying elements that increase the corrosion risk and often give ball hardnesses which are too high.…”
Section: Enhanced Doped Gold Bonding Wires With Higher Strength / Purmentioning
confidence: 99%
“…An earlier study of the Au-lTi alloy in wire form (5,6) demonstrated that a precipitation strengthening phenomenon is also observed after the material is drawn to a fine wire. In both cases, samples of the material are initially solution treated in a vacuum at approximately 850°C, water quenched and then cold worked as appropriate, followed by a heat-treatment at a lower temperature to develop maximum strength.…”
Section: The Enhanced Strengthening Of Au-iti Achievable In Fine Wirementioning
confidence: 99%
“…This was consistent with a limited diffusion path length of oxygen into the alloy, even when this is heavily cold worked. An experiment was undertaken to test whether oxidation is involved in the strengthening of Au-I Ti fine wire (5). A length of Au-ITi wire that had been drawn down to 25Jlm was divided into two halves.…”
Section: Anomalous Strengthening Mechanismmentioning
confidence: 99%
See 1 more Smart Citation